Long-time behaviour and self-similarity in a coagulation equation with input of monomers - Costa, Fernando Pestana da (2006)
For a coagulation equation with Becker-Doring type interactions and time-independent monomer input we study the detailed long-time behaviour of nonnegative solutions and prove the convergence to a self-similar function